PENGARUH SUMBER AIR BERSIH, JAMBAN, DAN POLA ASUH TERHADAP STUNTING PADA BALITA DENGAN DIARE SEBAGAI VARIABEL INTERVENING - Al Ihsan; Muchsin Riviwanto; Darwel Darwel (Poltekkes Kemenkes Semarang, 2020)
Stunting is one of the main challenges that is currently faced by the health sector in the world and in developing countries, including Indonesia. Stunting is caused by a direct factors consisting of the amount of nutrient intake and a history of infectious diseases, and indirect factors such as availability and patterns of home consumption, inadequate parenting, and inadequate clean water and sanitation. The highest prevalence of stunting toddlers in the city of Padang based on the 2017 nutritional status monitoring report (PSG) is in the working area of Air Dingin Health Center, where Balai Gadang Village has the highest prevalence of stunting toddlers at 22.2%. This study aims to determine the environmental factors that have a direct and indirect effect on stunting in toddlers in Balai Gadang Village. This study is an analytical research design. The subjects of the study were families with stunting toddlers and inadequate sanitation facilities with a sample of 38 families. Data collection was conducted from January to June 2019 by reviewing the annual report of Air Dingin’s Health Center, observing sanitation facilities, interviewing, and laboratory tests on clean water. The statistical test that has been applied is path analysis method with multiple regression test. The results of the path analysis showed that there was a direct effect of variable diarrhea duration, E. coli levels in clean water sources, and the application of unhygienic and non-sanitary parenting to stunting. Indirect effects through diarrhea duration variables, ie E. coli levels in clean water sources and non-sanitary family toilet quality on stunting